2018
DOI: 10.1093/tbm/ibx063
|View full text |Cite
|
Sign up to set email alerts
|

Communication of cancer-related genetic and genomic information: A landscape analysis of reviews

Abstract: Cancer-related genetic and genomic testing (CGT) is changing cancer care by personalizing care options, leading to an era of precision medicine. Advances in and increased use of CGT add complexity to clinical communication. This landscape analysis assessed published reviews of communication issues related to CGT and discusses implications for practice and behavioral research. A comprehensive electronic literature search was conducted of peer-reviewed literature reviews on studies related to CGT communication p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 71 publications
1
54
0
Order By: Relevance
“…To date, there have been only a handful of systematic reviews focusing on the experiences of cancer patients related to genomic testing and most of them focused on germline testing rather than somatic testing and the implications on personalised therapies . While those systematic reviews explored important matters such as psychological distress, communication preferences, and decision‐making processes, none of them focused on the understanding of genomic testing and information needs of cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there have been only a handful of systematic reviews focusing on the experiences of cancer patients related to genomic testing and most of them focused on germline testing rather than somatic testing and the implications on personalised therapies . While those systematic reviews explored important matters such as psychological distress, communication preferences, and decision‐making processes, none of them focused on the understanding of genomic testing and information needs of cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, research efforts to simplify such information for effective communication to the public are implied. Recent literature research on cancer-related genetic/genomic testing has exposed the inadequacy of effective provider-patient communication due, in part, to a lack of systematic studies in health literacy and communication [ 14 ]. This lack of research in communication practices by health professionals on cancer genetic risk and testing is further substantiated in a study by Hamilton et al [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In many developing and underdeveloped countries, it is not even fully certain whether canonical risk factors (lifestyle and environment) are a public concern, let alone genetic risk. In a recent review study on cancer-related genetic and genomic testing, a lack of existing research on awareness and communication of this matter in minority and underserved communities is revealed [ 14 ]. The case of Malaysia alone is an indication of general public ignorance.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] Genetic testing is now available for some hereditary cancers and is now an integral part of cancer prevention, early detection services, and treatment. [ 1 8 ] Cancer gene testing presents many challenges that could include access, cost, risks, benefits, privacy, stigmatization, discrimination, ethical issues, and psychosocial implications of the results. [ 9 10 ] Peterson et al .…”
mentioning
confidence: 99%
“…[ 9 10 ] Peterson et al . [ 8 ] found that genetic testing resulted in distress and alienation in some male partners of women who underwent genetic testing for breast cancer, but women who found that they have an increased risk for breast cancer became more engaged in risk reduction behaviors such as breast self-examinations, mammograms, and preventative surgeries. In spite of these challenges and issues, a study found that primary care providers expressed skepticism about the clinical value of genetic testing and were concerned about clients’ privacy issues and discrimination by insurance companies and employers.…”
mentioning
confidence: 99%